159 Myocardial fibrosis is associated with reduced coronary flow velocity reserve in end-stage renal disease. (4th June 2021) - Radhakrishnan, Ashwin; Pickup, Luke; Price, Anna; Law, Jonathan; Fabritz, Larissa; Senior, Roxy; Steeds, Richard P.; Ferro, Charles; Townend, JN
Abstract : Background: Uraemic cardiomyopathy is present in >70% of patients with end-stage renal disease (ESRD). Myocardial fibrosis is a hallmark of uraemic cardiomyopathy and is associated with an increased risk of heart failure and sudden cardiac death. Coronary microvascular dysfunction (CMD) is common in ESRD and is an adverse prognostic marker that may contribute to this increased mortality. In hypertrophic cardiomyopathy (HCM), a condition that shares phenotypical similarities with uraemic cardiomyopathy including hypertrophy, cellular disarray and fibrosis, a negative correlation exists between myocardial fibrosis and CMD, raising the possibility that fibrosis is the result of microvascular ischaemia. This study aimed to determine whether a similar relationship exists in ESRD. Methods: 15 patients with ESRD underwent transthoracic echocardiography, coronary flow velocity reserve (CFVR) assessment by Doppler echocardiography and 3Tesla cardiac magnetic resonance imaging. Subjects with known coronary artery disease, moderate/severe valvular heart disease, diabetes and uncontrolled hypertension were excluded. Coronary microvascular dysfunction was defined using a cut-off value of CFVR<2. Myocardial fibrosis was assessed using native T1 times – with higher T1 values representing increased fibrosis. Basal septal, mid-septal and global native T1 times were calculated. T2 times, a marker of myocardial oedema, were also calculated. Results: 5/15 (33%) subjects had CMD. Baseline data were similar between patients with and without CMD apart from higher calcium in the CMD group – table 1 . There were no differences in echocardiographic parameters apart from global longitudinal strain which was lower in the CMD group (-17% ± 1 vs -20% ± 2, p=0.02). There were significant negative correlations between CFVR and basal septal (r= -0.7, p=0.003), mid-septal (r= -0.5, p=0.037) and global T1 times (r= -0.6, p=0.012) – figure 1 . Basal septal T1 times were significantly elevated in subjects with CMD – median 1309ms (IQR 1301-1313) vs 1292ms (IQR 1281-1295), p=0.028. There was a trend towards increased mid-septal and global T1 times in the CMD group - figure 2 and table 2 . There was no difference in T2 times between the groups. Conclusions: This is the first study to show that, similar to HCM, increased myocardial fibrosis is associated with reduced CFVR in ESRD. Although causation cannot be demonstrated in this study, it raises the fascinating question of whether myocardial fibrosis is 'the chicken or the egg' in this inverse relationship. Further mechanistic studies are needed to confirm this association and to determine which is the primary pathology. It is likely that the interplay between myocardial fibrosis and CMD contributes to the significant cardiac mortality seen in ESRD. Conflict of Interest: None to declare